Performance Comparison of Mutual Funds and Sharia Mutual Funds - Kharisma Novita Sari; Moch Sulchan; Mimah Mutamimah (Penerbit Goodwood, 2021)
Purpose: This study aimed to examine the differences in the performance of Islamic mutual funds with mutual funds based on the Sharpe and Jensen method for the 2010-2020 periods in the Indonesian capital market. Research Methodology: The study uses a quantitative approach to the type of comparative research. The data used is secondary data from Otoritas Jasa Keuangan (OJK). The population used in this study is the capitalization of sharia mutual fund performance data with mutual funds, the periods 2010-2020 (monthly data) in the Indonesian capital market. Data analysis was carried out using the Sharpe and Jensen method and the Manova test with the help of the SPSS statistical program. Results: The results of this study indicate that there is no significant difference between the performance of Islamic mutual funds and mutual funds with the Sharpe and Jensen method. This shows that the return on the performance of Islamic mutual funds and mutual funds based on the Sharpe and Jensen method received will be relatively the same. Investment performance in mutual fund portfolio management is reflected in the Net Asset Value (NAV). Conclusions: The results show no significant difference in the performance of Islamic and conventional mutual funds, as measured by the Sharpe and Jensen methods. This indicates that returns from both types of funds are relatively similar, and investment performance, reflected in Net Asset Value (NAV), is influenced by the manager’s policies and strategies. Limitations: This research has been attempted and carried out in accordance with scientific procedures. However, it still has limitations; this research is limited to 2010 – 2020 with monthly data. Contributions: This research implies that this research can better contribute to the general public, academics, and investors to understand the performance of capital market investment instruments before they invest.